Robust Biplot Analysis of Natural Disasters in Indonesia from 2019 To 2021 - Hilda Venelia; Khoirin Nisa; Rizki Agung Wibowo; Mona Arif Muda (Jurnal Aplikasi Statistika & Komputasi Statistik, 2021)
Indonesia is one of the most natural disaster-prone countries in the world, frequently exposed to a range of hazards. Currently, Indonesia has 34 provinces and natural disasters that occur in each province are different, therefore it is necessary to analyze the mapping of natural disasters that often occur in each province to provide scientific analysis for risk management of the natural disasters. One of the quick steps in describing data that can be used is biplot analysis, as biplot analysis can describe a lot of data then summarized it into the form of a two-dimensional graph. The aim of this research is to map 34 provinces in Indonesia based on the incidence of natural disasters from 2019 to 2021 using robust biplot analysis. Based on the result, robust biplot analysis can explain 87,9% of the information on natural disasters in every province in Indonesia. Lampung, Bengkulu, Bangka Belitung, Special Region of Yogyakarta, North Sulawesi, West Sulawesi, Southeast Sulawesi, Gorontalo, East Nusa Tenggara, Bali, Maluku, West Maluku, Papua, and West Papua are provinces that have similar natural disaster characteristics. Flood, tornado and forest and land fires are natural disasters that often occur in Indonesia. The provinces that have the highest risk of flood, landslide, and tornado were West Java, Central Java, and East Java. Then, the provinces with the highest risk of forest and land fires were Aceh and South Kalimantan.